Coprescription of mood stabilizers in schizophrenia, dosing, and clinical correlates: An international study. (1st August 2020) - Lim, Wai Kwong; Chew, Qian Hui; He, Yan‐Ling; Si, Tian‐Mei; Chiu, Fung‐Kum Helen; Xiang, Yu‐Tao; Kato, Takahiro A.; Kanba, Shigenobu; Shinfuku, Naotaka; Lee, Min‐Soo; Park, Seon‐Cheol; Park, Yong‐Chon; et al.
Abstract: Objective: Studies examining coprescription and dosages of mood stabilizers (MSs) with antipsychotics for psychotic disorders are infrequent. Based on sparse extant data and clinical experience, we hypothesized that adjunctive MS use would be associated with certain demographic (e.g., younger age), clinical factors (e.g., longer illness duration), and characteristics of antipsychotic treatment (e.g., multiple or high antipsychotic doses). Methods: Within an Asian research consortium focusing on pharmaco‐epidemiological factors in schizophrenia, we evaluated rates of MS coprescription, including high doses (>1000 mg/day lithium‐equivalents) and clinical correlates. Results: Among 3557 subjects diagnosed with schizophrenia in 14 Asian countries, MSs were coprescribed with antipsychotics in 13.6% ( n = 485) of the sample, with 10.9% ( n = 53) on a high dose. Adjunctive MS treatment was associated (all p < 0.005) with demographic (female sex and younger age), setting (country and hospitalization), illness (longer duration, more hospitalizations, non‐remission of illness, behavioral disorganization, aggression, affective symptoms, and social–occupational dysfunction), and treatment‐related factors (higher antipsychotic dose, multiple antipsychotics, higher body mass index, and greater sedation). Patients given high doses of MSs had a less favorable illness course, more behavioral disorganization, poorer functioning, and higher antipsychotic doses. Conclusions: Schizophrenia patients receiving adjunctive MS treatment in Asian psychiatric centers are more severely ill and less responsive to simpler treatment regimens.